RCSD1-ABL1 Translocation Associated with IKZF1 Gene Deletion in B-Cell Acute Lymphoblastic Leukemia - Shawana Kamran; Gordana Raca; Kamran Nazir (Case Reports in Hematology)
The RCSD1 gene has recently been identified as a novel gene fusion partner of the ABL1 gene in cases of B-cell Acute Lymphoblastic Leukemia (B-ALL). The RCSD1 gene is located at 1q23 and ABL1 is located at 9q34, so that the RCSD1-ABL1 fusion typically arises through a rare reciprocal translocation t(1;9)(q23;q34). Only a small number of RCSD1-ABL1 positive cases of B-ALL have been described in the literature, and the full spectrum of clinical, morphological, immunophenotypic, and molecular features associated with this genetic abnormality has not been defined. We describe extensive genetic characterization of a case of B-ALL with RCSD1-ABL1 fusion, by using conventional cytogenetic analysis, Fluorescence In Situ Hybridization (FISH) studies, and Chromosomal Microarray Analysis (CMA). The use of CMA resulted in detection of an approximately 70 kb deletion at 7p12.2, which caused a disruption of the IKZF1 gene. Deletions and mutations of IKZF1 are recurring abnormalities in B-ALL and are associated with a poor prognosis. Our findings highlight the association of the deletion of IKZF1 gene with the t(1;9)(q24;q34) and illustrate the importance of comprehensive cytogenetic and molecular evaluation for accurate prediction of prognosis in patients with B-cell ALL.